Laboratory evaluation of a wearable head impact sensor for use in water polo and land sports - Cecchi, N. J.; Monroe, D. C.; Oros, T. J.; Small, S. L.; Hicks, J. W. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
The SIM-G is a waterproof head impact sensor that has been previously evaluated for use in a headband, but not yet in a mode of attachment suitable for water polo. For this study, a CADEX linear impactor was used to impact a Hybrid III headform while wearing either a headband or modified water polo cap, each housing a SIM-G. In both headgears, the SIM-G consistently underestimated peak linear acceleration (p < .001) and peak rotational velocity (p < .001), and consistently overestimated peak rotational acceleration (p < .001) relative to the headform. These inaccuracies are consistent with previous evaluations of the SIM-G, but notably, impact magnitudes did not differ between the different modes of attachment (p > .198). The proprietary SIM-G algorithm used for classifying false/true positives performed poorly at the back and crown impact locations in both the water polo cap and headband, but accuracy of this algorithm did not significantly differ between the water polo cap and headband (60.5% vs 49.4%, respectively). The SIM-G`s ability to correctly predict impact location also performed poorly in both headgears when impacts occurred at the crown location, but was significantly better overall in the water polo cap than the headband (80.2% vs 55.6%, respectively). These results demonstrate that the SIM-G exhibits shared limitations and a similar performance overall when placed in either a headband or water polo cap. Potential explanations for the inaccuracies of the SIM-G, as well as methods of optimizing its application in sports, are discussed.